SEMIOTIC ANALYSIS IN FORENSIC LINGUISTICS: THE MEANING OF SYMBOLS IN THE TEMPO NEWS OFFICE TERRORISM CASE - Muhammad Musawir; Rahma Fitri Alifah (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
Abstract The act of terror against the Tempo Newsroom through the delivery of physical symbols such as a pig’s head and rat carcasses represents a complex form of threatening communication laden with symbolic meaning. This study examines how the symbolic meanings of these acts of terror can be interpreted through a semiotic approach within the framework of forensic linguistics, and how such symbols function as a form of non-verbal threat communication. The objective of this research is to analyze the pig’s head and rat carcasses as cultural signs used in the context of intimidation against independent media. This qualitative descriptive research employs semiotic theories (Saussure and Peirce), Bourdieu’s theory of symbolic violence, and forensic linguistic analysis of indirect speech acts. Data were obtained through document analysis of online news reports, public statements, and relevant academic literature. The findings reveal that the pig’s head and rat carcasses function as symbolic representamen socially constructed as acts of humiliation and warning. These signs carry connotations of impurity, filth, and threats directed at press institutions as a means of controlling freedom of expression. The symbols serve as indirect speech acts that are coercive and intimidating. The study concludes that symbolic violence in the form of non-verbal physical terror can serve as an effective tool of domination, especially when interpreted within the socio-political and cultural context in which it occurs.